Health-behavior among 10th grade students in Istanbul within contexts of family, peer, and school - Yıldırım, Özlem. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
The World Health Organization regularly conducts a cross-national research “Health behavior in school-aged children” (HBSC), in various countries including Türkiye. The current study is a part of the general, nation-wide HBSC study in Türkiye. Its aim was to examine family, peer, and school contexts as psychosocial factors in relation to development of health-related behaviors and attitudes among the 10th grade students in stanbul. Research questions were directed to examine the relations of these psychosocial variables to perceived academic achievement, general life satisfaction, and mental health as broad outcomes and bullying as a risk behavior. The entire sample of the main study was selected to represent Türkiye, this study used its stanbul sample which consisted of 611 adolescents (288 females and 323 males) between ages 15-19, taken from 20 high schools. The required questions package and selected parts of optional questions package developed by the HBSC working team were used as the standard study questionnaire. Findings, in general, showed that adolescents’ positive evaluations of family, peer, and school factors were significantly associated with perceived academic achievement, general life satisfaction, and self-rated mental health. Parental monitoring, bonding, and family wealth were positively related to these broad outcome variables. School-related parental support was positively related to academic achievement. Neutrals (students neither bullying nor victimized) reported higher levels of parental monitoring and bonding. Yet, bully-victim groups did not differ in family wealth and parental disciplinary behaviors. Among peer variables, social competence and peer group approval by other teenagers did not correlate with broad outcome variables. Friendship quality positively correlated only with mental health. Yet, other sources of peer group approval (other students, parents, and teachers) correlated with all broad outcomes. No significant difference was present in social approval scores of bully-victim groups. Yet, there were significant group differences in social competence, friendship quality, academic achievement, general life satisfaction, and mental health scores in favor of neutrals? Last, school-related stress had negative and school-related satisfaction had positive correlations with broad outcomes. There were significant group differences in school stress but not in school satisfaction. In all variables except school stress, the neutral students got the highest scores while victims and bully-victims had the lowest scores. This research suggested that educational programs should target not only students themselves but also peers, teachers and parents. Peer guidance intervention programs, social skills training, empathy education seem important because bullying has negative effects especially on victims. Cooperative classroom atmosphere and consistent disciplinary methods should be used to deal with bullying and aggression among adolescents.
Keywords: Health behavior in adolescence.